Identification of a second tetracycline-inducible polypeptide encoded by Tn10. - Zupancic, T J (1980)
Three Tn10 polypeptides were detected by analyzing the proteins synthesized in ultraviolet light-irradiated Escherichia coli cells after infection with lambda::Tn10. One of these polypeptides was the previously identified 36,000-dalton TET polypeptide. The other two had approximate sizes of 25,000 and 13,000 daltons. The syntheses of both the TET polypeptide and the 25,000-dalton polypeptide were inducible by tetracycline in lambda-immune hosts. Similarly, the synthesis of the TET polypeptide was inducible in nonimmune hosts. However, the synthesis of the 25,000-dalton polypeptide was constitutive in nonimmune hosts. An amber mutation in a gene required for tetracycline resistance on lambda::Tn10 was isolated that eliminated the synthesis of the TET polypeptide in sup+ hosts but not the synthesis of the 25,000-dalton or the 13,000-dalton polypeptides. The expression of tetracycline resistance from wild-type Tn10 was found to be anomalous in E. coli strains carrying the amber suppressors supD, supE, and supF. In general, strains containing these nonsense suppressors were less resistant to tetracycline.